Pompeii Food and Drink (2010)
[Dt.:] Das Ziel des Forschungsprojekts ist die Erforschung (ohne Ausgrabungen) der in Pompeji vorhandenen Einrichtungen, die in Verbindung zur Lagerung, Verteilung, Zubereitung und Verzehr von Nahrung stehen. Die Seite informiert über die aktuellen Vorgänge im Projekt und liefert darüber hinaus einige Hintergrundinformationen über die Stätten am Golf von Neapel. - [Engl.:] Goal of the research project is to analyze the patterns of daily life by a noninvasive study of the structures that are associated with the storage, distribution, preparation, serving, and consumption of food and drink in ancient Pompeii. The site informs on the current activities of the project and provides some background information on the sites of the Gulf of Naples.